2005
DOI: 10.1073/pnas.0507358102
|View full text |Cite
|
Sign up to set email alerts
|

The highly conserved cardiac glycoside binding site of Na,K-ATPase plays a role in blood pressure regulation

Abstract: The Na,K-ATPase contains a binding site for cardiac glycosides, such as ouabain, digoxin, and digitoxin, which is highly conserved among species ranging from Drosophila to humans. Although advantage has been taken of this site to treat congestive heart failure with drugs such as digoxin, it is unknown whether this site has a natural function in vivo. Here we show that this site plays an important role in the regulation of blood pressure, and it specifically mediates adrenocorticotropic hormone (ACTH)-induced h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
196
1
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 175 publications
(208 citation statements)
references
References 62 publications
10
196
1
1
Order By: Relevance
“…In transgenic mice with mutated ␣1 and ␣ 2 Na ϩ pumps, in which ␣ 1 is rendered ouabain sensitive and ␣ 2 is ouabain resistant, ACTH induces a profound, Digibindsensitive hypertension within 24 h (20). The implication is that acute inhibition of ␣ 1 , which increases tone and contractility in isolated arteries (120), can elevate BP.…”
Section: How Does Low-dose Ouabain Augment Contractility?mentioning
confidence: 99%
See 2 more Smart Citations
“…In transgenic mice with mutated ␣1 and ␣ 2 Na ϩ pumps, in which ␣ 1 is rendered ouabain sensitive and ␣ 2 is ouabain resistant, ACTH induces a profound, Digibindsensitive hypertension within 24 h (20). The implication is that acute inhibition of ␣ 1 , which increases tone and contractility in isolated arteries (120), can elevate BP.…”
Section: How Does Low-dose Ouabain Augment Contractility?mentioning
confidence: 99%
“…But the NCX and ␣ 2 Na ϩ pumps are colocalized in PM microdomains at PM-SER junctions (Fig. 2) (56,106) where these two transport systems appear to function cooperatively (4,30 (20), and this increases myogenic tone (50,120) by a direct effect on the contractile machinery.…”
Section: Ouabain Antagonism As a Therapy For Hypertensionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is still difficult to draw definitive conclusions regarding the specific function of these molecules in pathophysiology. Although the studies by Dostanic-Larson et al (2) strongly support the suggestion that endogenous cardiac glycoside-like compounds are the naturally occurring ligand, they do not eliminate the possibility that other steroid-like (or, indeed, nonsteroidal) molecules, either previously identified or novel, may play this functional role. Nevertheless, this important work does clearly demonstrate that a naturally occurring regulator must exist and that its interaction with the cardiac glycoside binding site of the Na,K-ATPase plays a role in blood pressure regulation.…”
mentioning
confidence: 81%
“…However, the strong evolutionary conservation of this binding site among almost all species has suggested that important physiological functions may involve recognition of this site by endogenous agents. The work of Dostanic-Larson et al in this issue of PNAS (2) demonstrates that the cardiac glycoside binding site of Na,K-ATPase plays an important physiological role in blood pressure regulation. It is reported that ACTH-induced hypertension is abolished when the interaction of cardiac glycosides with the Na,K-ATPase is disrupted.…”
mentioning
confidence: 99%